2017
DOI: 10.1103/physreva.95.062324
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement, coherence, and redistribution of quantum resources in double spontaneous down-conversion processes

Abstract: We study the properties of bisqueezed tripartite Gaussian states created by two spontaneous parametric down-conversion processes that share a common idler. We give a complete description of the quantum correlations across all partitions, as well as of the genuine multipartite entanglement, obtaining analytical expressions for most of the quantities of interest. We find that the state contains genuine tripartite entanglement, in addition to the bipartite entanglement among the modes that are directly squeezed. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 73 publications
(160 reference statements)
0
46
0
Order By: Relevance
“…For example, recently it has been shown that in double parametric pumping of a superconducting microwave cavity, coherence between photons in separate frequency modes can arise because of the absence of which-way information in the frequency space [35]. Similarly, in a double spontaneous down-conversion processes, it has been shown that coherence in photons in the signal is induced due to lack of which-path information for the photons emitted in the idler [36]. Coherence has also found applications in quantum metrology [37].…”
Section: Coherence: a New Measure Of Wave Naturementioning
confidence: 99%
“…For example, recently it has been shown that in double parametric pumping of a superconducting microwave cavity, coherence between photons in separate frequency modes can arise because of the absence of which-way information in the frequency space [35]. Similarly, in a double spontaneous down-conversion processes, it has been shown that coherence in photons in the signal is induced due to lack of which-path information for the photons emitted in the idler [36]. Coherence has also found applications in quantum metrology [37].…”
Section: Coherence: a New Measure Of Wave Naturementioning
confidence: 99%
“…The pump at f p1 produces TMS between f 1 and f 2 , while the pump at f p2 coherently couples f 3 with f 1 . In the BS scheme [35], the pump tones are applied at f p1 = f 1 + f 2 and f p2 = f 2 + f 3 , directly producing TMS correlations between the pairs. See Table I for the exact frequencies used.…”
Section: Methodsmentioning
confidence: 99%
“…The entangled microwave photons could also be used as a source for a quantum radar. Photons can be generated from vacuum by using not only one, but several pumps [11], aiming at using multimode correlations as a resource [12]. And there is more to it.…”
Section: Further Developmentsmentioning
confidence: 99%